Late- and post-glacial changes of shoreline on the northern side of the Forth valley and estuary - Smith, David Edward (The University of Edinburgh, 1965)
The generally accepted patterns of raised shorelines on the northern side of the Forth valley and estuary are substantially in error. This investigation has shown that a radically different pattern of raised shorelines exists in the area, and that from this pattern and the associated glacial features there may be interpreted the following general sequence of events: 1. During the Würm period, the Forth area was covered by a great ice sheet which depressed the crust of the earth beneath it. As the ice sheet began to retreat, and as the load decreased, the crust reacted by trying to maintain isostatic equilibrium, thus rising. During the retreat large quantities of water, which had been abstracted from the oceans during the build-up of this and other contemporary ice sheets, were returned to the oceans and world sea level rose. Thus by the time the Forth area began to be released from the ice and the sea was able to gain access, both isostatic and eustatic rise were in progress. This resulted in the formation of several displaced shorelines, which mark periods when isostatic and eustatic movement were in equilibrium. 2. Two (LG1-2) and probably four other (LG3-6) displaced shorelines were formed during this early period while the ice probably retreated without major interruption from Fife Ness to Leven. Each shoreline slopes down towards the east, demonstrating that maximum isostatic uplift lay in the west, and each shoreline is less steeply sloping than the one above it, suggesting regular uplift. 3. The six displaced shorelines are as follows: LG1 is the best developed. It slopes eastwards from a height of 90-92 feet O. D. at Anstruther to 75-78 feet O.D. at Fife Ness. It is associated with a prolonged halt of the retreating ice near the site of Anstruther. • LG2 is also well formed. It achieves 81y83 feet O. D. near Pittenweem, and slopes down to 68-69 feet O.D. at Fife Ness. It displays no definite association with a former ice front, but there are instances of parts having been formed in association ...